Controlling the Proliferation and Differentiation Stages to Initiate Periodontal Regeneration. (April 2013) - Chong, Li Yen; Chien, Li-Ying; Chung, Min-Chun; Liang, Kaicheng; Lim, Jason Chu-Shern; Fu, Jia Hui; Wang, Chi-Hwa; Chang, Po-Chun
<x xml:space="preserve">Abstract</x> The success of periodontal regeneration depends on the coordination of early cell proliferation and late cell differentiation. The aim of this study was to investigate whether the proliferation or differentiation stage predominantly promotes the initiation of periodontal regeneration. Critical-sized periodontal defects were surgically created on rat maxillae and filled with poly-(d, l-lactide-co-glycolide)–poly-d, l-lactide hybrid microspheres encapsulating platelet-derived growth factor (PDGF, a promoter of mitogenesis), simvastatin (a promoter of osteogenic differentiation), or bovine serum albumin (a control). The encapsulation efficiency and in vitro release profiles of the microspheres were determined by high-performance liquid chromatography and enzyme-linked immunosorbent assay. The maxillae were harvested after 10 or 14 days and assessed by micro-computed tomography, histology, and immunohistochemistry for regeneration efficacy and cell viability. The rapid release of PDGF was observed within the first week, whereas a slow release profile was noted for simvastatin. The PDGF-treated specimens demonstrated a significantly higher bone volume fraction compared with bovine serum albumin– (p < 0.05) or simvastatin-treated (p < 0.05) specimens at day 14. Histologically, active bone formation originating from the defect borders was noted in both the PDGF- and the simvastatin-treated specimens, and functionally aligned periodontal ligament fiber insertion was only observed in the PDGF-treated specimens. The significant promotion of mitogenesis by PDGF treatment was also noted at day 14 (p < 0.05). In conclusion, increased mitogenesis or osteogenic differentiation may stimulate osteogenesis, and the upregulation of mitogenesis by PDGF appears to play a role in the initiation of periodontal regeneration.